Resposta do meloeiro gália submetido a concentrações de nitrogênio e potássio na água de irrigação - Vieira, Régis Cavalcante (Universidade Federal Rural do Semi-Árido, 2018)
Fertigation is one of the most relevant techniques to provide an increase in crop productivity and profitability, so that it can be evaluated through research that can be performed through the medium of nutrient absorption curves and the use of fertilizer doses, for several times no The word may be present in some cases with regard to economy and environment. The use of fertirrigation through the monitoring of nutrient concentration in the soil solution has been reported as a technique that brings benefits to the use, contribution with reduction of production costs and environmental degradation with the reduction of the use of fertilizers. The objective of this study was to improve the fertigation technique by controlling the soil solution ions in the melon crop. The experiment was developed out in a greenhouse, where the solutions of the N and K in the soil solution were evaluated. The objective of this study was to design experimental blocks (DBC) with four blocks and five treatments, totaling 20 experimental plots and 2 replications, totaling 40 experimental plots. The. Adopted were the main factors of N and K (0, 50, 100, 150 and 200%) that were combined to form 5 treatments. The treatments of N-NO3 and K were corrected from a considered standard dose (100%), corresponding to 168 and 234 mg / L-1 of N and K, and after, combined, the stimuli were assimilated: 0-0.50 -50, 100-100, 150-150 and 200-200. The degree of nutrient accumulation at 45 days in melon leaves was observed in the following order: N> K> Ca> Mg> P> Fe; Mn; Zn. The N1K1 treatment presented its advantages regarding the growth variables, already for the Chlorophyll and Internal Carbon Concentration variables, the N4K4 treatment presented the results. An applied fertigation is not important for the variables of Colloid Diameter, Chlorophyll and Instant Efficiency of Carboxylation.
Monografia
Keywords: Cucumis melo L.; Controle de íons; Cultivo protegido; Nitrato e potássio; Fertirrigação; Cucumis melo L.; Ion control; Protected cultivation; Nitrate e potassium; Fertigation; CIENCIAS AGRARIAS::AGRONOMIA